Chemical control of whitefly (Bemisia tabaci) biotype B (Hemiptera: Aleyrodidae) in cotton crop - Silva, Bruna Guimarães da; Côrrea, Fernando Rezende; Silva, Nelmício Furtado da; Cavalcante, Wendson Soares da Silva; Ribeiro, Daniele Ferreira; Rodrigues, Estevão (Brazilian Journal of Science, 2023)
Cotton crop (Gossypium hirsutum) is an oilseed with herbaceous-shrubby habit. Whitefly (Bemisia tabaci), which is a polyphagous insect, presents direct and indirect damage to this crop through ingestion. The main method of controlling this pest is the use of insecticides, with different mechanisms of action. The objective was to verify the efficiency after application of different insecticide options for the control of whitefly nymphs in the cotton crop. The treatments were different: 1-Witness; 2-Ciantraniliprole (35 g a.i.ha-1); 3-Ciantraniliprole (40 g a.i.ha-1); 4-Ciantraniliprole (45 g a.i.ha-1); 5-Ciantraniliprole (50 g a.i. ha-1); 6-Ciantraniliprole + mineral oil (35 g a.i.ha-1 + 756 g a.i.ha-1); 7-Acetameprid + Pyriproxifen (60 g a.i.ha-1 + 30 g a.i.ha-1); 8-Abamectin + Ciantraniliprole (20 g ai ha-1 + 5 g a.i ha-1) and 9-Sulfoxaflor + adhesive spreader (96 g a.i.a ha-1 + 4.5 g a.i.a ha-1). Two foliar applications were carried out, with an interval of 10 days (23/02/21 and 05/03/21), using the costal equipment with CO2 pressurization, equipped with a spray bar, with a spray volume of 150 L ha-1. At the time of applications, the culture was between stages (V7 and B4), respectively. An evaluation was carried out before the infestation and after application 3, 7 and 10 after the first one (DA1A); 3,7 and 10 after the second application (DA2A). The evaluations were made by counting the number of whitefly nymphs in 10 leaves of each plot with the aid of a binocular stereoscopic magnifying glass (20X). Data were transformed (√x+K) by the statistical software SASM®. Being interpreted by the Scott-Knott 5% mean test. It is concluded that the application Acetamiprid + Piriproxifem (60 g ai ha-1 + 30 g ai ha-1) and Ciantraniliprole at doses (40 and 50 g ai ha-1) stood out in relation to the other treatments.